Explaining the intention-behaviour gap in gluten free diet adherence: The moderating roles of habit and perceived behavioural control - Kothe, E.; Sainsbury, Kirby; Smith, L.; Mullan, Barbara (Sage Publications Ltd, 2014)
Adherence to a strict gluten free diet (GFD) is the only treatment for coeliac disease. Nonetheless, many individuals with the disease struggle to achieve and maintain strict adherence. While the theory of planned behaviour is useful for predicting GFD adherence, an intention-behaviour gap remains. The aim of this study was to investigate the roles of habit and perceived behavioural control in moderating the intention-behaviour relationship in GFD adherence. A significant three-way interaction was found such that the association between intention and adherence was dependent on both perceived behavioural control and habit. Implications for both theory and intervention design are discussed.